Alpha-fetoprotein for Diagnosis, Prognosis, and Transplant Selection - Trevisani, Franco; Garuti, Francesca; Neri, Andrea (Seminars in Liver Disease, 2019)
Reliable biomarkers are of great clinical value in predicting cancer occurrence/recurrence, anticipating its detection at an asymptomatic stage, supporting the radiological diagnosis, stratifying patients for prognosis and proper therapy, and measuring the response to treatment. Despite the plethora of biomarkers proposed for hepatocellular carcinoma (HCC), the first one identified, α-fetoprotein (AFP), remains the most utilized. This article reviews the lights and shadows of AFP as a surveillance test for patients at risk of HCC, and as a diagnostic test for those with chronic liver disease and a suspected hepatic mass. Moreover, the article scrutinizes the large body of evidence supporting the prognostic relevance of AFP in patients undergoing both curative and palliative treatment of HCC and the growing importance attributed to this biomarker (as a static or a dynamic variable) in the selection of potential candidates for liver transplantation. In fact, the inclusion of AFP among transplant criteria would improve the ability of identifying poor candidates due to an unacceptable risk of HCC recurrence regardless of tumor burden, and of adopting flexible morphological selection criteria.
Keywords: α-fetoprotein; hepatocellular carcinoma; diagnosis; prognosis; liver transplantation